Mediating effect of creative self-efficacy on the influence of knowledge sharing towards innovative work behavior among millennial knowledge workers - Apriadi Cundawan; Nony Kezia Marchyta; Thomas Santoso (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
The influx of new workers is starting to be dominated by the millennial generation. This shift provides a demographic advantage for Indonesia as millennial generations are generally aware of the technology. However, to maximize this advantage, the millennial knowledge workers need to have innovative work behavior. The purpose of this study was to examine the effect of knowledge sharing mediated by creative self-efficacy on innovative work behavior among millennial knowledge workers in Surabaya, Indonesia. This research was conducted with a quantitative approach using a questionnaire-based survey involving 145 respondents who were millennial knowledge workers in Surabaya, based on the knowledge worker groups, they were 56 employees, 44 independents, and 45 business operators. This research was analyzed using explanatory research using partial least square. The finding showed that among millennial knowledge workers in Surabaya, knowledge sharing significantly influenced innovative work behavior, meanwhile, creative self-efficacy partially mediated the influence between knowledge sharing and innovative work behavior. However, further examination based on the knowledge worker category showed that creative self-efficacy did not have a mediating effect on the business operator group.